Find the solution for \( -0.5 x-3.69=x-1.9-2.39 \)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To solve the equation \( -0.5x - 3.69 = x - 1.9 - 2.39 \), let's first simplify the right side: \[ x - 1.9 - 2.39 = x - 4.29 \] So the equation now looks like: \[ -0.5x - 3.69 = x - 4.29 \] Next, let's collect all the \( x \) terms on one side and the constant terms on the other side. Adding \( 0.5x \) to both sides gives: \[ -3.69 = x + 0.5x - 4.29 \] This simplifies to: \[ -3.69 = 1.5x - 4.29 \] Now, add \( 4.29 \) to both sides: \[ -3.69 + 4.29 = 1.5x \] This results in: \[ 0.6 = 1.5x \] Finally, divide both sides by \( 1.5 \): \[ x = \frac{0.6}{1.5} = 0.4 \] So the solution is: \[ x = 0.4 \] Keep cracking those equations! They can be as satisfying to solve as slaying a dragon in a video game! 😄